An Evaluation of the Implementation of the Three Doctors Policy in Primary Care Units in Trat Province - Prasittinawa, Jirayut (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2026)
This cross-sectional descriptive research aimed to evaluate the effectiveness of the Three-Doctor (3 หมอ) Policy implementation in primary care units in Trat Province, to identify success factors, barriers, and to propose developmental guidelines. The study employed a quantitative approach using structured questionnaires. The sample consisted of 460 health personnel across three groups, selected using disproportionate stratified sampling to ensure adequate representation: Doctor 1 (Village Health Volunteers; n=372), Doctor 2 (Public Health Officers; n=70), and Doctor 3 (Family Medicine Physicians; n=18), along with 430 service recipients selected through multi-stage sampling calculated using Taro Yamane formula for personnel and Cochran's formula for citizens. Data were collected using two structured questionnaires validated by three experts, with Cronbach's alpha coefficients ranging from 0.87 to 0.93. Data were analyzed using descriptive statistics, one-way ANOVA with Tukey's HSD post-hoc test, Pearson correlation, and multiple regression analysis. The results revealed that overall implementation effectiveness was at a high level. All personnel groups demonstrated high levels of policy knowledge (Mean = 3.85–4.03) and operational performance (Mean = 3.76–4.21), with Doctor 3 scoring highest. Operational performance differed significantly among the three groups (F = 3.672, p = 0.026), confirmed by Tukey's HSD showing Doctor 3 significantly higher than Doctor 2 (p = 0.019). Policy knowledge did not differ significantly (F = 1.318, p = 0.268). Knowledge showed a strong positive correlation with performance (r = 0.658, p < 0.01). The factor most influencing citizen satisfaction was the service quality of Doctor 3 (Beta = 0.321), with all predictors explaining 68.7% of satisfaction variance (R² = 0.687; VIF range = 1.32–2.18). Citizens reported high levels of policy awareness (Mean = 3.72) and satisfaction (Mean = 4.07). Primary barriers included excessive workload (38.2–66.7%), resource deficiency—particularly among Doctor 3 (77.8%)—and the lack of an integrated health information system (61.1%). Recommendations include developing an integrated electronic health information system, reallocating personnel and resources commensurate with workload, and enhancing digital literacy training for elderly Village Health Volunteers.